The Challenge of Fiscal Decentralization in Transition Countries - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2002)
This paper examines key aspects of the ongoing decentralization process in transition economies and identifies areas where the present systems can have potentially adverse impacts on both service delivery and macroeconomic performance. We discuss three critical principles of a sound and efficient decentralized fiscal system-and then show the contrasts between these and actual trends and policies in transition countries.